Physicochemical evaluation and in vitro release studies on itraconazolium sulfate salt - Neeraj Kumar; Shishu Goindi; Gulshan Bansal (Elsevier, 2014)
To counter the poor aqueous solubility of itraconazole (ITC), its sulfate salt (ITCSUL) was synthesized and characterized by 1H NMR, MS, FTIR, DSC, XRPD, DLS and SEM. Antifungal properties of ITCSUL were confirmed against different fungal pathogens by broth microdilution method. Enhanced solubility of the salt in various pharmaceutical solvents was observed. Approximately 5.5 fold increase in percentage drug release from ITCSUL than that of ITC in 3 h was observed. Further, the physical mixtures of ITCSUL with two cyclodextrins; β-cyclodextrin (β-CD) and HP-β-cyclodextrin (HP-β-CD) were prepared in 3 M ratios. The in vitro release studies of CD mixtures of ITC and ITCSUL exhibited markedly enhanced dissolution in comparison to ITC and ITCSUL respectively. The promising in vitro performance of ITCSUL and ITCSUL CD mixtures along with advantage of expedient preparation suggest their potential applications in designing a better oral drug delivery system.